Osteonecrosis in paediatric acute lymphoblastic leukaemia: Incidence, risk factors, radiological patterns and evolution in a single‐centre cohort. (1st April 2022) - Brivio, Erica; Cossio, Andrea; Borra, Davide; Silvestri, Daniela; Prunotto, Giulia; Colombini, Antonella; Verna, Marta; Rizzari, Carmelo; Biondi, Andrea; Conter, Valentino; Valsecchi, Maria Grazia; Balduzzi, Adriana
Summary: Osteonecrosis (ON) is a well‐known sequela of paediatric acute lymphoblastic leukaemia (ALL) treatment. Incidence differs substantially among studies and the clinical significance of radiological findings is not fully established. We analysed 256 consecutive patients with ALL treated in our Institution between October 2010 and December 2016. Within the cohort, 41 developed ON, with a mean 5‐year cumulative incidence of 18.5 (standard error, SE, 5.7)% overall. The mean (SE) 5‐year cumulative incidence of ON was 12.7 (2.1)% after censoring upon stem cell transplantation (SCT) and/or relapse. Patients aged ≥10 years and patients allocated to the high‐risk stratum had a 10‐fold and fivefold higher risk of ON respectively. The risk of ON was more than double in relapsed patients, whereas no significant impact of gender, immunophenotype and SCT was demonstrated. Multiple lesions (median four joints involved per patient) were detected by magnetic resonance imaging in all but one patient, with the knee being the most affected joint. Lesions affecting convex joint surfaces experienced the worst evolution, whereas most lesions on diaphyses and concave surfaces remained radiologically stable or disappeared during follow‐up. ON has a high prevalence in paediatric ALL, presenting with multiple lesions. Lesions involving convex surfaces were at higher risk of radiological deterioration.